Radioiodine Uptake in Incidentally Detected Neuroendocrine Tumor: Correlative Imaging With FDG PET/CT and 68Ga-DOTATATE PET/CT. (29th October 2022) - Hod, Nir; Lantsberg, Sophie; Levin, Daniel
Abstract: Radioiodine whole-body scintigraphy has long been used for detection of differentiated thyroid carcinoma with high avidity in functioning thyroid tissues. However, uptake is not completely specific, and "false-positive" uptake in nonthyroidal tumors have rarely been reported. Herein, we present a case of incidentally detected neuroendocrine tumor showing high radioiodine uptake initially suspected to be thyroid metastasis. Correlative imaging with FDG PET/CT and 68 Ga-DOTATATE PET/CT is presented, and literature survey is discussed. We conclude that neuroendocrine tumor should be added to the reported list of neoplasms that can show "false-positive" uptake representing a potential interpretative pitfall.